MANIFESTASI MODERASI PERSPEKTIF BUKU AL-WASATHIYAH KHASISAH AL-UMMAH AL-ISLÂMIYYAH: ANALISIS TEORI DAN IMPLEMENTASI - Ridwan, Muhamad; Hidayat, Nur; Arnanda, Niko Septa (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2023)
This study aims to determine the manifestation of moderation (wasathiyah) from the perspective of the book al-Wasathiyah Khasisah al-Ummah al-Islâmiyyah and its implementation in the educational environment (school). This study uses library research methods (library research). The primary data source used in this research is the book al-Wasathiyah Khasisah al-Ummah al-Islâmiyyah, while the secondary data source is a number of books and journal articles related to this research. The data analysis process in this study uses the content analysis method which includes: (1) Identifying and describing; (2) Interpret and analyze; (3) Drawing conclusions. The results of this study indicate that Muhammad Abû al-Fath al-Bayânûnî gave the concept of meaning to this moderation with the meanings al-i'tidal and at-tawazun, these values ??are manifested in the aspects of aqîdah, ubûdiyah, morals, mu'amalah and rule of law, and the manifestation of this moderation can be implemented in the educational environment through character education methods which include: teaching, exemplary, setting priorities, praxis priorities and reflection.